Hypoglycemic and Antihyperglycemic Potential of Flavonoid Fraction from Citrus sinensis (L.) Osbeck in Normoglycemic and Diabetic Rats - Jesús Alfredo Araujo-León; Maira Rubi Segura-Campos; Rolffy Ortiz-Andrade; Priscila Vazquez-Garcia; Daniela Carvajal-Sánchez; Ángel Cabañas-Wuan; Avel Adolfo González-Sánchez; Jonatan Uuh-Narvaez; Juan Carlos Sánchez-Salgado; Inés Fuentes-Noriega; Zhelmy Martín-Quintal (MDPI AG, 2023)
Diabetes is one of the most prevalent diseases worldwide, and the search for therapeutic alternatives in developing countries has been focused on natural products, primarily from plants. This study evaluated the antihyperglycemic and hypoglycemic activities of the albedo (FA) and flavedo (FF) flavonoid fractions obtained from orange peels (often discarded) in normoglycemic Wistar rats. The flavonoid fractions were identified and quantified using HPLC-UV-DAD and compared with glibenclamide, repaglinide, saxagliptin, and acarbose. Additionally, both fractions were tested in a streptozotocin (65 mg/kg)/nicotinamide (100 mg/kg)-induced diabetic model. In normoglycemic rats, the highest glucose variation (%VG) occurred during the first hour after FA (112.8%) and FF (105.30%) administration at 100 mg/kg, indicating a hypoglycemic effect. In diabetic rats, FF at 100 mg/kg showed the highest %VG (140.41%) during the first hour after administration. HPLC-UV-DAD analysis revealed the presence of hesperidin (HSP) and naringenin (NGN), with the highest concentrations found in FA (HSP: 41.41%; NGN: 10.75%). These findings suggest potential antihyperglycemic effects of FA and FF fractions, possibly attributed to the presence of HSP and NGN. The results obtained in this work lay the foundations to explore the therapeutic applications of orange peels for controlling hyperglycemia in diabetes. In conclusion, our results suggest a reevaluation and revalorization of orange peels, as they contain pharmaceutically relevant flavonoids.